Stephenie Meyer author of the Twilight series - Mortensen, Lori 1955- (North Mankato, Minnesota Capstone Press, 2017)
"Discusses the life and works of author Stephenie Meyer"--
Famouse people
Includes bibliographical references (page 31) and index
1 2 13 15
Keywords: Meyer, Stephenie -- 1973- -- Juvenile literature; Authors, American -- 21st century -- Biography -- Juvenile literature